(untitled) (Journal of The Colloquium for Information Systems Security Education, 2017)
With the healthcare industry facing a new reality, healthcare applications are steadily impacting the mobility and security of how caregivers and hospitals are authorized to access vital information. In this Chapter, a proposed privacy-preserving EHR system using ciphertext-multi authority attribute-based encryption (CPMA-ABE) will be built. In this system, patients can encrypt their EHRs and store them on semi-trusted cloud servers such that servers do not have access to sensitive EHR contexts. Meanwhile patients maintain full control over access to their EHR files, by assigning fine-grained, attribute-based access privileges to selected data users, while different users can have access to different parts of their EHR. In addition, security issues for mobile health are discussed as well.